2008
DOI: 10.1194/jlr.m700281-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of apolipoprotein A-V on plasma triglyceride, lipoprotein size, and composition in genetically engineered mice

Abstract: Transgenic (Tg) mice that overexpress the human apolipoprotein A-V gene (APOA5) yet lack an endogenous mouse apoa5 gene (APOA5 Tg mice) were generated. Subsequently, the effect of human apoA-V expression on plasma triglyceride (TG) concentration and lipoprotein and apolipoprotein distribution was determined and compared with that in mice deficient in apoA-V (apoa5 2/2 mice). NMR analysis of plasma lipoproteins revealed that APOA5 Tg mice had a very low VLDL concentration (26.4 6 7.7 nmol/dl), whereas VLDL in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…APOA5 can enhance lipoprotein lipase (LPL) activity to accelerate the rate of LPL-mediated triglyceride hydrolysis to regulate triglyceride metabolism (Schaap et al, 2004;Rensen et al, 2005). It had been found that several haplotypes of APOA5 gene were related with the significant changes in triglyceride level (Grallert et al, 2007;Nelbach et al, 2008). In rat, the percentage of body fat was significantly correlated with serum triglyceride (Paik and Yearick, 1978), and in the young females and male pigs, the triglyceride level was positively correlated with backfat thickness (Mersmann and MacNeil, 1985).…”
Section: Introductionmentioning
confidence: 91%
“…APOA5 can enhance lipoprotein lipase (LPL) activity to accelerate the rate of LPL-mediated triglyceride hydrolysis to regulate triglyceride metabolism (Schaap et al, 2004;Rensen et al, 2005). It had been found that several haplotypes of APOA5 gene were related with the significant changes in triglyceride level (Grallert et al, 2007;Nelbach et al, 2008). In rat, the percentage of body fat was significantly correlated with serum triglyceride (Paik and Yearick, 1978), and in the young females and male pigs, the triglyceride level was positively correlated with backfat thickness (Mersmann and MacNeil, 1985).…”
Section: Introductionmentioning
confidence: 91%
“…c Statistical analysis and calculation were only conducted in women. (32). There are numerous reports on the association of genetic variants of APOA5 with low HDL-C levels, such as rs662799, rs651821, and rs2075291 in Japanese populations (33) and Chinese populations (34).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, several loss-of-function and null apoA-V alleles are associated with both reduced plasma apoA-V levels and elevated plasma TG ( 12, 13 ), yet other studies have found both positive and negative associations between plasma apoA-V and TG concentrations ( 7,14,15 ). Moreover, recent studies in mice have found a positive correlation between plasma apoA-V and TG concentrations ( 16,17 ).…”
mentioning
confidence: 97%
“…In humans, several loss-of-function and null apoA-V alleles are associated with both reduced plasma apoA-V levels and elevated plasma TG ( 12, 13 ), yet other studies have found both positive and negative associations between plasma apoA-V and TG concentrations ( 7,14,15 ). Moreover, recent studies in mice have found a positive correlation between plasma apoA-V and TG concentrations ( 16,17 ).Despite its apparent impact on intravascular TG-rich lipoprotein lipolysis and clearance, a peculiar characteristic of apoA-V is that its plasma concentration is in the range of 100-200 µg/l, which is ‫ف‬ 10,000-fold lower than apoA-I and ‫ف‬ 1,000-fold lower than apoA-IV and corresponds to ‫ف‬ 1 molecule of apoA-V for every 1,000 VLDL particles ( 18,19 ). This presents a conundrum as to how an apolipoprotein circulating at such low levels could exert such a potent effect on plasma TG metabolism and concentration.…”
mentioning
confidence: 99%